The Effect of Working Mother on Children’s Cognitive Achievement - Latifah Dian Iriani; Susilo Nur Aji Cokro Darsono; Maisaroh Samaee (Universitas Muhammadiyah Yogyakarta, 2023)
Children's cognitive is the main role in increasing human capital. Female labor force participation is important not only for supporting economic growth but also for human capital. Moreover, female labor force participation can reduce the income gap based on gender and it gives women opportunity to increase their skills. Workers in the informal sector are more dominant than a worker in the formal sector in almost developing countries, especially women who are already married. Therefore, the effect of female labor participation is still on debated. This research aims to know the different effects of working mothers based on the formal and informal sectors on children’s cognitive development. This study is using IFLS 2, IFLS 3, IFLS 4, and IFLS 5. The sample is mother who have children aged 0-3 years old. Children’s cognitive is measured by national examination scores in Elementary school and Junior High school. Moreover, this study used a fixed-effect method to reduce the bias effect. The result shows that working mother in the formal sector affects children cognitively higher than children with working mother in the informal sector. Working mother in the formal sector has a higher impact on the short-term than long-term. Caused by mother education in the formal sector is higher than working mothers in the informal sector. Moreover, a working mother can be alleviated maternal education which means a higher maternal education can increase children's cognitive. Although maternal education has a higher impact when children are in elementary school and it tends to decrease when children are in Junior high school. Several children have a negative and significant effect on children's cognition but birth order has a positive and significant effect on children cognitive.